The brushmaker's daughter - Kacer, Kathy, 1954- (Holocaust remembrance book for young readers., 2020)
In 1939 Berlin, Germany, twelve-year-old Lillian Frey and her blind father find shelter with brush factory owner Otto Weidt after being evicted from their home and pursued by Nazi soldiers. Otto makes brushes for the Nazi army, but secretly employs blind Jews, like Mr. Frey, offering them a safe haven and shelter. But with the Gestapo constantly watching them, Lillian worries their newfound safety is only temporary.